Safety and Potential Efficacy of Escalating Dose of Ustekinumab in Pediatric Crohn Disease (the Speed-up Study): A Multicenter Study from the Pediatric IBD Porto Group of ESPGHAN. Issue 6 (8th September 2022) - Yerushalmy-Feler, Anat; Pujol-Muncunill, Gemma; Martin-de-Carpi, Javier; Kolho, Kaija-Leena; Levine, Arie; Olbjørn, Christine; Granot, Maya; Bramuzzo, Matteo; Rolandsdotter, Helena; Mouratidou, Natalia; Hradsky, Ondrej; Scarallo, Luca; et al.
Abstract : Objectives: Escalation of the ustekinumab (UST) maintenance dosage was effective in adults with Crohn disease (CD), but no data are available for children. We evaluated the effectiveness and safety of dose escalation of UST in pediatric CD. Methods: This was a retrospective multicenter study from 25 centers affiliated with the IBD Interest and Porto groups of ESPGHAN. We included children with CD who initiated UST at a standard dosing and underwent either dose escalation to intervals shorter than 8 weeks or re-induction of UST due to active disease. Demographic, clinical, laboratory, endoscopic, imaging, and safety data were collected up to 12 months of follow-up. Results: Sixty-nine children were included (median age 15.8 years, interquartile range 13.8–16.9) with median disease duration of 4.3 years (2.9–6.3). Most children were biologic (98.6%)- and immunomodulator (86.8%)- experienced. Clinical response and remission were observed at 3 months after UST escalation in 46 (67%) and 29 (42%) children, respectively. The strongest predictor for clinical remission was lower weighted Pediatric Crohn Disease Activity Index (wPCDAI) at escalation ( P = 0.001). The median C-reactive protein level decreased from 14 (3–28.03) to 5 (1.1–20.5) mg/L ( P = 0.012), and the fecal calprotectin level from 1100 (500–2300) to 515 (250–1469) µg/g ( P = 0.012) 3 months post-escalation. Endoscopic and transmural healing were achieved in 3 of 19 (16%) and 2 of 15 (13%) patients, respectively. Thirteen patients (18.8%) discontinued therapy due to active disease. No serious adverse events were reported. Conclusions: Two-thirds of children with active CD responded to dose escalation of UST. Milder disease activity may predict a favorable outcome following UST dose escalation.